DEVELOPMENT OF OCCUPATIONAL HEALTH NURSING FROM YESTERDAY TO TODAY - ÜNER, ELİF (Göbeklitepe Medical Science Journal, 2022)
Nurses in health services; It is reported that if nursing services are provided in line with accessible targets and implementation plans, they will make great contributions to increasing occupational health. In this direction, occupational health nursing is a branch of public health nursing in which nursing knowledge and skills are used professionally in the working environment as an important team member of occupational health and safety. He is the key person working professionally in order to protect and improve health in the developing and changing working environment. Today, the exact number of occupational health nurses is not known, and their active duties include; employment examinations, periodic examinations, chronic diseases, work accidents, emergency intervention in occupational diseases and health promotion practices are included. This field of study includes nursing practices using public health theories and principles. Occupational health nursing in the world and in Turkey today; Various standards related to education and application areas have been determined. However, the changing and expanding regulations show differences. In this context, the review has been prepared to criticize the current situation, education and legal dimension of occupational health nursing and to inform occupational health nurses and nursing students